Bioprospecting of Plant Growth-Promoting Traits of Pseudomonas Sp. Strain c3 Isolated from the Atacama Desert: Molecular and Culture-Based Analysis - Maldonado-Soto, J (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Soil microorganisms that inhabit extreme environments have unique metabolic capacities and/or physical structures that allow them to survive in oligotrophic conditions. The bioprospecting of unknown bacteria in the context of current advances in genome mining is fundamental for the discovery of natural products with novel properties or applications. In this study, the plant growth-promoting and biocontrol traits of a Pseudomonas isolated from soil associated with plants from the Atacama Desert were characterized by whole-genome sequencing and in vitro assays. A high-quality genome draft of Pseudomonas sp. isolate C3 was obtained. An automated biosynthetic gene cluster analysis using antiSMASH 6.0 revealed the presence of a cluster of genes for the biosynthesis, regulation, and transport of the metabolite 2,4-diacetylphloroglucinol, which showed a high protein sequence identity (>89%) with a validated orthologous gene cluster from another Pseudomonas. In addition, via an in vitro assay, the biocontrol activity of Pseudomonas sp. isolate C3 against Botrytis cinerea, Monilinia fructicola, Phytium sp., Alternaria sp., Geotrichum candidum, and Fusarium oxysporum was corroborated. Finally, through KofamKOALA, the presence of genes involved in different metabolic pathways of plant growth-promoting traits was identified, which was corroborated by in vitro assays. This study provides information obtained from genomic analyses and culture tools on a bacterial isolate from the Atacama Desert characterized by plant growth-promoting capacities and biocontrol activity. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.